BIBLIOMETRIC ANALYSIS AND SYSTEMATIC LITERATURE REVIEW OF SHARIA COMPLIANCE RESEARCH: ANALISIS BIBLIOMETRIK DAN TINJAUAN LITERATUR SISTEMATIS TERHADAP PENELITIAN TENTANG KEPATUHAN SYARIAH - Anggraini, Misi; Novia, Aidil; Wira, Ahmad (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2024)
This research aims to determine the map of research development and systematically explore articles about sharia compliance using bibliographic studies and Systematic Literature Reviews (SLR). Research data was obtained through the Scopus database. The study was conducted over a 10-year period from 2013 to 2023, looking for keys to sharia compliance by searching publications and discarding applications on the Scopus website. A total of 93 research papers were obtained. The data obtained was analyzed via PRISMA to obtain accurate data. SSS implementation steps occur in three phases: identification, validation, and feasibility. The SSS process selected 63 articles from 29 identified articles, and the selected articles were analyzed further. Based on the mapping visualization results using VOSviewer, the sharia compliance study was divided into 21 clusters based on keywords and 10 clusters based on the author's words. Thanks to the Publish or Perish application, the highest score was achieved in 2022 with the number of publications reaching 20 journal articles. Rating agencies and professional journals now publish academic publications on sharia compliance. The institution that publishes many related journals is the Journal of Islamic Marketing. In addition, Mr. Rabbani and Mr. Mustafa Raza are the most productive research authors in the field of Sharia compliance from 2013 to 2023.